2016
DOI: 10.1590/1519-6984.05115
|View full text |Cite
|
Sign up to set email alerts
|

Fruit color preference by birds and applications to ecological restoration

Abstract: Ecological restoration aims to retrieve not only the structure but also the functionality of ecosystems. Frugivorous birds may play an important role in this process due to their efficiency in seed dispersal. Color perception in these animals is highly developed, and then the colors of fleshy fruits may provide important clues for choosing plant species for restoration plans. This study aims to integrate bird color preferences and restoration of degraded areas, with an objective to evaluate the potential attra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 36 publications
1
8
1
2
Order By: Relevance
“…The discrimination of red and black fruits from other colors is consistent with empirical studies, which frequently suggest that red and black fruits are preferred by birds (36)(37)(38). The fact that fruit color was not related to variance in frugivore diversity also supports previous research that has suggested that fruit or seed size may be the only trait that responds to selection from frugivores (11).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The discrimination of red and black fruits from other colors is consistent with empirical studies, which frequently suggest that red and black fruits are preferred by birds (36)(37)(38). The fact that fruit color was not related to variance in frugivore diversity also supports previous research that has suggested that fruit or seed size may be the only trait that responds to selection from frugivores (11).…”
Section: Discussionsupporting
confidence: 87%
“…In the first ("Fruit_color1" in SI Appendix, Table S2), fruits that were qualitatively "bright" (e.g., red, orange, yellow, or white) were assigned to 1 and "dull" fruits (e.g., black, brown, green) assigned to 0. In the next three categorization schemes, fruits that were red or black were assigned a 1, and other fruits were assigned 0; this is based on empirical measurements of fruit preference in birds (36)(37)(38); indeed, Schmidt et al (ref. 54, p. 551) noted a "global prevalence" of red and black fruits, likely driven by conspicuousness of those colors to avian frugivores.…”
Section: Methodsmentioning
confidence: 99%
“…The preference for the red color may be explained by its attractiveness to birds (Whitney, 2005;Gagetti et al, 2016). The fact that insects did not show a preference for the red color in our study goes against previous studies (Takahara and Takahashi, 2016) and may be explained by the high effectiveness of the chemical treatments in our study region.…”
Section: Grape Lossescontrasting
confidence: 80%
“…La mayoría de estas especies presentan frutos en bayas y drupas de colores vistosos como evidencia del síndrome de dispersión para aves (fig. 8), debido a que los frutos rojos y negros son consumidos más que otros colores en áreas restauradas en bosques tropicales (Gagetti et al, 2016). El análisis del síndrome de dispersión de las especies espontáneas evidenció una mayor contribución de la zoocoria (78%) en la dispersión de especies espontáneas del bosque de referencia, principalmente aves, en comparación con las dispersadas por el viento (22%; tabla 2).…”
Section: Discussionunclassified